2018
DOI: 10.1038/s41418-018-0209-1
|View full text |Cite
|
Sign up to set email alerts
|

Impact of elevated anti-apoptotic MCL-1 and BCL-2 on the development and treatment of MLL-AF9 AML in mice

Abstract: Many acute myeloid leukaemias (AMLs) express high levels of BCL-2 and MCL-1, especially after therapy. To test the impact of these anti-apoptotic proteins on AML development and treatment, we used haemopoietic reconstitution to generate MLL-AF9 AMLs expressing BCL-2 or Mcl-1 transgenes. AMLs with elevated BCL-2 or MCL-1 had a higher proportion of mature myeloid cells but, like conventional MLL-AF9 AMLs, were readily transplantable. Short-term cell lines established from multiple primary AMLs of each genotype w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 63 publications
2
21
0
Order By: Relevance
“…We observed that the IL-17B-IL-17RB axis can be specifically induced by Ara-C. Our data support the strategy of targeting the IL-17B-IL-17RB axis to overcome chemoresistance in AML, and suppression of IL-17B or IL-17RB is accompanied by a modulation of bcl-2 family proteins that prime the cell for apoptosis after chemotherapy. In agreement with this observation, recent studies have demonstrated that inhibition of bcl-2 family proteins render AML cells more susceptible to chemotherapeutic agents (49,50). However, bcl-2 family proteins are essential for survival and function during many important developmental process (51)(52)(53)(54), and inhibition of bcl-2 may have an unacceptable side effect.…”
Section: Discussionmentioning
confidence: 62%
“…We observed that the IL-17B-IL-17RB axis can be specifically induced by Ara-C. Our data support the strategy of targeting the IL-17B-IL-17RB axis to overcome chemoresistance in AML, and suppression of IL-17B or IL-17RB is accompanied by a modulation of bcl-2 family proteins that prime the cell for apoptosis after chemotherapy. In agreement with this observation, recent studies have demonstrated that inhibition of bcl-2 family proteins render AML cells more susceptible to chemotherapeutic agents (49,50). However, bcl-2 family proteins are essential for survival and function during many important developmental process (51)(52)(53)(54), and inhibition of bcl-2 may have an unacceptable side effect.…”
Section: Discussionmentioning
confidence: 62%
“…The sudden emergence of effective MCL1 inhibitors has broadened the horizon for strategies used to target MCL1, and studies have also confirmed the efficacy of using MCL1 inhibitors in combination with other BCL-2 family inhibitors 98 , 102 104 . Several MCL1 inhibitors, including S63845 95 , AMG 176 96 , AZD5991 97 , S64315 105 , and AMG 397 ( https://clinicaltrials.gov ), are already being investigated in the clinical stage, and the future of their application in the treatment of chemoresistance is encouraging.…”
Section: Targeting Mcl1 In Cancer Treatmentmentioning
confidence: 99%
“…Indeed, venetoclax (ABT-199), an oral BCL-2 inhibitor, has been approved for the treatment of chronic lymphocytic leukemia and elderly patients with AML ( DiNardo et al, 2019 ). Similarly, inhibition of MCL-1 via S64315 or AMG-176 as a single-agent therapy or in combination with BCL-2 inhibitor and other drugs is in clinical trials for AML treatment ( Anstee et al, 2019 ; Caenepeel et al, 2018 ; Ramsey et al, 2018 ; Teh et al, 2018 ). Although BCL-2 itself is an important player in tumorigenesis and represents an important therapeutic target, in vivo stimulation of the expression of pro-apoptosis proteins in AML treatment (e.g., BIM) has not been studied in preclinical models ( Shukla et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%